Economic distress and resurgence in US central cities: Concepts, causes, and policy levers - Yolanda K. Kodrzycki; Ana Patricia Mu\~noz (Federal Reserve Bank of Boston, 2013)
This paper provides a review of the literature on U.S. central city growth and distress during the second half of the twentieth century.It finds that city growth tended to be higher in metropolitan areas with favorable weather, higher growth, and greater human capital, while distress was strongly correlated with city-level manufacturing legacy. The article affirms that distress has been highly persistent, but that some cities have achieved resurgence through a combination of strong leadership, collaboration across sectors and institutions, clear and broad-based strategies, and significant infrastructure investments. Finally, the article explores measurement issues by comparing two methodologies used to identify poorly performing central cities: comparisons across a comprehensive national cross-section of cities and comparisons within smaller samples of similar cities. It finds that these approaches have produced similar assessments of a city's status, except in some cases where the city's progress has been uneven across time or with respect to alternative criteria.
Keywords: R11; R12; R23; R58; O15; 330